ANALISIS PROKSIMAT, MINERAL ESENSIAL, DAN CEMARAN LOGAM BERAT PADA TERIPANG Acaudina molpadioides DARI PERAIRAN PALOH KALIMANTAN BARAT - Safitri, Ikha; Helena, Shifa; Warsidah, Warsidah; Sari Juane Sofiana, Mega (JFMR (Journal of Fisheries and Marine Research), 2021)
Acaudina molpadioides was found along the coast of Paloh, Sambas Regency, West Kalimantan in recent months. This sea cucumber known as one of the typical foods of the coastal community of Karimun. This species has similarities with Paracaudina sp. belonging to the Caudinidae family. Proximate content, essential minerals and heavy metal contamination have never been carried out on A. molpadioides from Paloh waters. Nutrition in this biota will varies in different places. It is due to different environmental influences in terms of physical and chemical parameters. Proximate analysis were carried out. They were content of water, ash, protein and fat. The essential minerals analyzed from the samples were zinc (Zn), copper (Cu), iron (Fe) and manganese (Mn) using Atomic Absorption Spectrophotometer (AAS). Heavy metal contamination of Pb and Cd was also measured by AAS. Moisture, ash, fat and protein content of A. molpadioides were 36.23%; 7.61%; 0.004% and 3.35% respectively. The essential minerals detected in A. molpadioides were Zn (0.054 ppm), Fe (3.35 ppm) and Mn (0.150). Heavy metal contamination of Pb and Cd was not detected from A. molpadioides samples.